Recurso de agravo de instrumento: avanços, retrocessos e perspectivas - Araújo, Alex Carlos Capura de (2023)
The present work aimed to understand the interlocutory appeal, elucidating the mitigation of the taxativity of the hypotheses of applicability and the central controversies of the recourse regime thought for the civil procedure code of 2015. the methodology used was a bibliographic review of descriptive nature, which was arranged on selected scientific content, which followed linked to the theme of this study in the databases. based on the research carried out, it was possible to verify that the impact of the mitigated taxativity rendered by the superior court of justice in article 1.015 of the code of civil procedure applicable to the interlocutory appeal" was to increase to more hypotheses of appealability via interlocutory appeal. it is important to remember that some possibilities are exceptional and must be analyzed on a case-bycase basis. the case law of the superior court of justice has allowed that some situations not included in the exhaustive list may be subject to an interlocutory appeal, provided that the urgency and the uselessness of an appeal via appeal are proven. even so, there is great uncertainty regarding the preclusion of the situations in which the interlocutory appeal is allowed by case law, which leaves doubts as to the application of the theory of mitigated taxability